Philippine financial almanac - Litiatco, Vicki J. (Venture Unlimited, 1997)
A biannual publication alternating with the Philippine Banking Almanac. It includes different sectors in the Philippine financial system that play a crucial role in the economic development of our nation. It also contains a compendium of interesting and informative articles on the various sectors contained in the publication, and vital information on the individual companies comprising each sector.